Web-Based Directory of Libraries and Information Centers in Malaysia / Law Hui Sheng - Law, Hui Sheng (2005)
Dyflicia (Directory of Libraries and Information Centers in Malaysia) is a we-based system that provides information on libraries and information centers in Malaysia. This system provides an interactive search and browse function to make the retrieving of information faster and easier for the users. The Dyflicia' s members include the Directors of a library or Information Center and the System Administrators. The Directors will register his or hers institution and they can maintain the information from time to time. The System Administrators will use the Management subsystem to manage the institution records and registration, members and the feedback from the users. This report begin with the introduction part. The introduction part consists of the project definition, objectives, target users, scope, limitation schedule, expected outcome and the report layout. It is followed by the literature review which includes the approaches to literature review, existence system analysis and comparison and technical aspects discussion. Next is the methodology for developing Dyflicia. Here, the waterfall life-cycle model which will be used is discussed. The report continues with the system analysis which includes the user functional and non-functional requirements. The technical requirement analysis is also included in this chapter which covers the software and hardware requirements. The next chapter is the system design which includes the system structure design, application architecture design (context diagram and data flow diagram), system database diagram, and interface design. After system design, comes the system implementation, which discusses the implementation aspects of Dyflicia. System testing comes next which discusses the testing that is done on Dyflicia. The report ends with system evaluation and conclusion which stated Dyflicia's strength, limitations, future enhancement, problems faced and a brief conclusion for the whole theses.